KNOWLEDGE AND ATTITUDE TOWARDS EXPRESSED BREAST MILK AMONG WORKING MOTHERS IN HARARI REGIONAL STATE, ETHIOPIA, 2021: EXPRESSED BREAST MILK - Arif Hussen Jamie; Elias Sertse Gebremedhin (STIKes Mandala Waluya Kendari, 2022)
Background: World health organization (WHO) rules in the beginning six month the child should be given breast milkonly, so mothers coming back to work should have a good knowledge about appropriate expression of breast milk. The main goal of the research was to determine knowledge and attitude toward expressed breast milk among working mothers in Harari region, Ethiopia, 2021 Methods:A cross-sectional study was done on 385 employed mothers for analysis of data SPSS 22 used. Results: Over all knowledge and attitude about expressed breast milk were 36% and 44%respectivly. Conclusion: the study showed there was knowledge gap in the expressing and storing of breast milk. More exertion is essential to be done by the health professionals ineducating mothers on way of expression, storing and timings of storage of expressed breast milk of breast.